Plasma concentrations of oleoylethanolamide and other acylethanolamides are altered in alcohol‐dependent patients: effect of length of abstinence. (22nd May 2016) - Garcia‐Marchena, Nuria; Pavon, Francisco J.; Pastor, Antoni; Araos, Pedro; Pedraz, Maria; Romero‐Sanchiz, Pablo; Calado, Montserrat; Suarez, Juan; Castilla‐Ortega, Estela; Orio, Laura; Boronat, Anna; Torrens, Marta; et al.
Abstract: Acylethanolamides are a family of endogenous lipid mediators that are involved in physiological and behavioral processes associated with addiction. Recently, oleoylethanolamide (OEA) has been reported to reduce alcohol intake and relapse in rodents but the contribution of OEA and other acylethanolamides in alcohol addiction in humans is unknown. The present study is aimed to characterize the plasma acylethanolamides in alcohol dependence. Seventy‐nine abstinent alcohol‐dependent subjects (27 women) recruited from outpatient treatment programs and age‐/sex‐/body mass‐matched healthy volunteers (28 women) were clinically assessed with the diagnostic interview PRISM according to the DSM‐IV‐TR after blood extraction for quantification of acylethanolamide concentrations in the plasma. Our results indicate that all acylethanolamides were significantly increased in alcohol‐dependent patients compared with control subjects ( p < 0.001). A logistic model based on these acylethanolamides was developed to distinguish alcohol‐dependent patients from controls and included OEA, arachidonoylethanolamide (AEA) and docosatetraenoylethanolamide (DEA), providing a high discriminatory power according to area under the curve [AUC = 0.92 (95%CI: 0.87–0.96), p < 0.001]. Additionally, we found a significant effect of the duration of alcohol abstinence on the concentrations of OEA, AEA and DEA using a regression model ( p < 0.05, p < 0.01 and p < 0.001, respectively), which was confirmed by a negative correlation ( rho = −0.31, −0.40 and −0.44, respectively). However, acylethanolamides were not influenced by the addiction alcohol severity, duration of problematic alcohol use or diagnosis of psychiatric comorbidity. Our results support the preclinical studies and suggest that OEA, AEA and DEA are altered in alcohol‐dependence during abstinence and that might act as potential markers for predicting length of alcohol abstinence. Abstract : Plasma concentration of oleoylethanolamide (OEA) and other acylethanolamides are increased in alcohol‐dependent patients in abstinence. OEA, arachidonoylethanolamide (AEA) and docosatetraenoylethanolamide (DEA) are the best explanatory variables to distinguish alcohol‐dependent patients in abstinence from controls. Plasma concentration of OEA, AEA and DEA are negatively correlated to the duration of the abstinence.